Validation of a short cognitive battery to screen for fitness‐to‐drive of people with multiple sclerosis. (22nd June 2018) - Akinwuntan, A. E.; Backus, D.; Grayson, J.; Devos, H.
Abstract : Background and purpose: Some symptoms of multiple sclerosis (MS) affect driving. In a recent study, performance on five cognitive tests predicted the on‐road test performance of individuals with relapsing‐remitting MS with 91% accuracy, 70% sensitivity and 97% specificity. However, the accuracy with which the battery will predict the driving performance of a different cohort that includes all types of MS is unknown. Methods: Participants ( n = 118; 48 ± 9 years of age; 97 females) performed a comprehensive off‐road evaluation that lasted about 3 h and a standardized on‐road test that lasted approximately 45 min over a 2‐day period within the same week. Performance on the five cognitive tests was used to predict participants' performance on the standardized on‐road test. Results: Performance on the five tests together predicted outcome of the on‐road test with 82% accuracy, 42% sensitivity and 90% specificity. Conclusions: The accuracy of predicting the on‐road performance of a new MS cohort using performance on the battery of five cognitive tests remained very high (82%). The battery, which was administrable in <45 min and cost ~$150, was better at identifying those who actually passed the on‐road test (90% specificity). The sensitivity (42%) of the battery indicated that it should not be used as the sole determinant of poor driving‐related cognitive skills. A fail performance on the battery should only imply that more comprehensive testing is warranted.